Antennal heart morphology supports relationship of Zoraptera with polyneopteran insects. (3rd July 2014) - WIPFLER, BENJAMIN; PASS, GÜNTHER
Abstract The antennal hearts of the zorapteran Zorotypus hubbardi and of two psocopteran species (Caecilius sp., Embidopsocus sp.) are described in detail and compared to those of other insects. In Zorotypus, the ampullae of this organ are located dorsally of the antennal base. They are attached to the frontal cuticle of the head capsule and laterally suspended by two delicate bands of connective tissue. The associated muscles comprise a well‐developed M. interampullaris and a M. ampulloaortica, which together act as dilators of the ampullae. The connected antennal vessel has a very thin wall and is uniform along its entire length. In the two studied psocopterans the ampullae are likewise connected to the head capsule and have two additional elastic bands. In Caecilius sp. the anterior band is muscular, while in Embidopsocus sp. it is the posterior one. The psocopteran antennal hearts have no additional musculature. Antennal hearts with a musculature configuration resembling that of Zoraptera are known only from Dictyoptera, Phasmatodea and some orthopterans. This condition thus might be a synapomorphy of a polyneopteran subgroup including Zoraptera.